Endothelial precursor cell cross‐match using Tie‐2‐enriched spleen cells. Issue 12 (12th October 2017) - Daniel, Volker; Süsal, Caner; Scherer, Sabine; Tran, Hien; Gombos, Petra; Trojan, Karina; Sadeghi, Mahmoud; Morath, Christian; Opelz, Gerhard
Abstract: Background: Non‐HLA antibodies against human endothelial progenitor cells (EPC) in pre‐transplant recipient serum can have a deleterious influence on the graft. EPC enriched from peripheral blood have been commonly used for EPC cross‐matching. In the present study, we describe cross‐matches using EPC enriched from fresh or frozen‐thawed spleen cell preparations, thereby widening the sample source for deceased‐donor cross‐matching and retrospective studies. Methods: EPC cross‐matches were performed retrospectively using spleen cells and the flow cytometric XM‐ONE cross‐match test kit. Results: Healthy controls (n = 28) showed no IgG antibodies against EPC. When sera of 11 random dialysis patients were studied, 2 patients (18%) exhibited IgG EPC antibodies. When pre‐transplant sera of 20 kidney graft recipients with good long‐term graft outcome (serum creatinine 1.0 ± 0.2 mg/dL measured 2463 ± 324 days post‐transplant) were investigated using frozen‐thawed and then separated Tie‐2‐enriched spleen cells of the original transplant donor, 3 patients (15%) had pre‐transplant IgG EPC antibodies. When pre‐transplant sera of 5 patients with intra‐operative graft loss were studied employing the original donor spleen cells, 4 (80%) patients showed IgG EPC antibodies. Conclusions: Cross‐matches with spleen cell‐derived EPC using the XM‐ONE assay are technically possible. Our very preliminary experience suggests clinical relevance.